Influence of Contact Network Topology on the Spread of Tuberculosis - Pinto, Eduardo R. [UNESP]; Nepomuceno, Erivelton G.; Campanharo, Andriana S. L. O. [UNESP] (Springer Nature, 2019)
This paper presents the influence of the complex networks topology on the spread of Tuberculosis with the use of the Individual-Based Model (IBM). Five complex network models were used with the IBM, namely, random, small world, scale-free, modular and hierarchical models. For every model, we applied the usual topological properties available in literature for the characterization of complex networks. Afterwards, we verified the topological effect of the contact networks in the evolution of tuberculosis and it was observed that different contact networks result in different epidemic thresholds for the spread of tuberculosis. More specifically, we noted that networks that have greater heterogeneity of connections need a lower, however when the value of the infection rate is large, the number of individuals infected are similar. It is believed that this observation may contribute to actions to reduce and eradicate the disease.
Keywords: Complex networks; Complex systems; Individual-Based Model; Topological effect; Tuberculosis